The Impact of the Prohibition of Non–Audit Services on the Profitability of Big-4-affiliated Audit Firms in Bangladesh - Md Jahidur Rahman; Mo Lai Lan Phllis; Lam Mo (Emerald Publishing Limited, 2016)
The purpose of this paper is to study the impact of the prohibition of certain non-audit services by the Securities and Exchange Commission (SEC) of Bangladesh on the profitability of the audit firms which are affiliated with Big-4 international audit firms. This paper is based on personal in-depth interviews with the Big-4-affiliated audit firms. A qualitative approach, in a way which is descriptive and illustrative, is adopted in this research. This research provides evidence for the fact that audit services are the most significant and stable source of income for an audit firm. Although respondents generally admit that non-audit services might be more profitable, they all agree that audit services are indeed the core operations of an audit firm. Findings in this paper reveal a contemporary picture of the auditing profession in Bangladesh and elucidate the impact that the implementation of Corporate Governance Order 2006 has on an audit firm's profitability. This research is the first in-depth study of the impact of the prohibition of non-audit services on the profitability of the Big-4-affiliated audit firms in Bangladesh. Financial reporting regulatory authorities in Bangladesh or other developing countries may find the findings in this paper useful.